Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Rasio Aktivitas terhadap Nilai Perusahaan pada Perusahaan Makanan dan Minuman yang Terdaftar di ISSI Tahun 2018-2022 - Oktaria Syafira; Asyari Asyari (Transformasi: Journal of Economics and Business Management, 2024)
This research was carried out against the background because currently food and beverage companies are growing rapidly and many investors are starting to invest their capital in companies in this sector. Before investing capital, what you need to look at in companies in this sector is their company value, however there are several companies whose company value decreases every year. The purpose of this research is to find out how much investment decisions, funding decisions and activity ratios influence company value in food and beverage companies included in ISSI. In this study, researchers used a 5 year period/time period from 2018-2022. Researchers used a quantitative approach in this research. The sampling technique used in this research is the purposive sampling method/using certain criteria. Then the population used in this research was 61 companies, and after conducting sample criteria, 12 food and beverage companies were included in the ISSI for the 2018-2022 period. Furthermore, the data analysis used/used by researchers in this research is panel data analysis which combines cross sections (observing many companies at one time) and time series (time series). This test shows the results that variables X1 (investment decisions) and X3 (activity ratio) have a significant positive influence on company value, while variable X2 (funding decisions) has an insignificant negative influence on company value. And the results of the simultaneous test of variables X1 (investment decisions), X2 (funding decisions) and X3 (activity ratio) influence Y (company value).